Literacy and Inclusion Levels of Organic Fertilizer in Boyolali Organic Farmer Association - Malik Malik Cahyadin; Raden Kunto Adi; Yayan Yayan Suherlan; Bekti Wahyu Utami; Rendi Fathoni Hadi; Emi Emi Widiyanti (LPPM UNS, 2025)
Organic farming products are beneficial not only to people's well-being, but also to the environment's long-term viability. One of the cooperatives producing organic agricultural products in Central Java Province is the Boyolali Organic Farmers Association (APOB). This association's problems are twofold, namely: the lack of organic fertilizer literacy and organic fertilizer inclusion for managers and members. Therefore, this study attempts to assess the levels of organic fertilizer literacy-inclusion and empowering business institutions. The period of assessment began in July and ended in August 2025. The primary data were collected using focus group discussion and in-depth interview involving 15 APOB managers and members. The method was descriptive statistics. The findings reveal that the literacy level of organic fertilizer was 66.29%. Meanwhile, the inclusion level was 72.18%. There is 5.89% difference level between literacy and inclusion. This condition illustrates that the level of organic fertilizer inclusion is slightly higher than the literacy level. Policy implications are delivered to APOB managers to increase organic fertilizer literacy and inclusion through training programs and workshops. Furthermore, the local government can facilitate business development and mentoring in organic fertilizer production and utilization.